P-18 Neurological carer well being programme: a new initiative to support carers of people living with palliative neurological conditions. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Hunt, Kimberley; Fletcher, Julie; Cochrane, Yvonne
Abstract : Background: The day hospice has observed a growing demand for services in relation to patients suffering neurological conditions, in particular the need to support their carers. Caring for someone with a progressive neurological condition can have a significant impact on their life both psychologically, emotionally and practically and a hospice setting is an ideal place to provide this support. Aims: To provide a specific carers well-being programme for carers of people with a palliative neurological condition. The aim of the programme is to develop carers' resilience through learning more about living with someone with this condition, enhancing their coping strategies and developing new ones, learning new practical skills, sharing experiences and gaining support from others in similar circumstances. To increase partnership working with MND specialist nurse and Parkinson's disease specialist nurse. Method: The hospice has gained funding from the Board of Trustees to extend the number of carers' groups. In view of this, we have liaised with specialist nurses representing patients with Motor neurone disease and Parkinson's disease to discuss offering carer support. A planning meeting is in the process of being established involving multi-disciplinary professionals from the hospice and specialist nurses to discuss and plan the well-being programme carers. A pilot group is planned to start in July 2016. Results: The Pilot will be evaluated through a carer questionnaire and feedback from the specialist teams. The results will be collated and presented to the Audit Group for approval of an agreed action plan. If this pilot is successful, the group may be offered twice yearly. Conclusion: Living with a neurological condition can have a major effect both emotionally and psychologically on carers. This programme is an excellent opportunity to ensure they are supported both emotionally and psychologically improving quality of life for both carers and their loved ones.